GC-MS Analysis of Bioactive Compounds in Methanolic Extracts of Papaver decaisnei and Determination of Its Antioxidants and Anticancer Activities - Ahmed Aj. Jabbar; Fuad O. Abdullah; Kamaran K. Abdulrahman; Yaseen Galali; Abdullah Sh. Sardar (Journal of Food Quality)
The Papaver L. plant (Papaver decaisnei) has ethnobotanical records in many countries including Iraqi Kurdistan. The current study investigates the methanol (99.9%) extracts (10 μg/mL) of roots, leaves, and flowers of Papaver decaisnei in terms of phytochemistry by gas chromatography-mass spectrophotometry GC-MS, in vitro antioxidant activity by radical scavenging and reducing power assays, and finally, the anticancer actions as IC50 (inhibitory concentration at 50%) against human colorectal adenocarcinoma (Caco-2), mammary cancer cells (MCF-7), and human cervical carcinoma (HeLa) cells. The results showed 22, 19, and 17 chemicals for roots, leaves, and flowers of P. decaisnei, respectively. The prevalent organic compounds of P. decaisnei were alkaloids (62.03%), phenolics (55.43%), fatty acids (42.51%), esters (32.08%), terpenoids (25.59%), and phytosterols (15.68%), namely, roemerine (70.44%), 9,12,15-octadecatrien-1-ol (37.45%), hexadecanoic acid (33.72%), decarbomethoxytabersonine (24.49%), and γ-sitosterol (11.22%). The antioxidant activity of plant organs was within 39.1–143.5 μg/mL for DPPH, 135.4–276.4 μg/mL for ABTS, 12.4–34.3 μg/mL for FRAP, and 42.6–75.8 μg/mL for CUPRAC assays. The anticancer of P. decaisnei was found as 125.3–388.4 μg/mL against all tested cell lines (Caco-2, MCF-7, and HeLa). The detected alkaloids and bioactivity of P. decaisnei encourage future isolation of those remarkable alkaloids (reomerine) for potential usage in the pharmaceutical industry.